3(5k+3)-18k+6+2=

Simple and best practice solution for 3(5k+3)-18k+6+2= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(5k+3)-18k+6+2= equation:


Simplifying
3(5k + 3) + -18k + 6 + 2 = 0

Reorder the terms:
3(3 + 5k) + -18k + 6 + 2 = 0
(3 * 3 + 5k * 3) + -18k + 6 + 2 = 0
(9 + 15k) + -18k + 6 + 2 = 0

Reorder the terms:
9 + 6 + 2 + 15k + -18k = 0

Combine like terms: 9 + 6 = 15
15 + 2 + 15k + -18k = 0

Combine like terms: 15 + 2 = 17
17 + 15k + -18k = 0

Combine like terms: 15k + -18k = -3k
17 + -3k = 0

Solving
17 + -3k = 0

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-17' to each side of the equation.
17 + -17 + -3k = 0 + -17

Combine like terms: 17 + -17 = 0
0 + -3k = 0 + -17
-3k = 0 + -17

Combine like terms: 0 + -17 = -17
-3k = -17

Divide each side by '-3'.
k = 5.666666667

Simplifying
k = 5.666666667

See similar equations:

| m/6=4.4 | | 2.5/4 | | 107-3x=5x-19 | | (7x+3)+6y=180 | | -3z+21-z=8-7 | | 8-5(12+8)= | | y=0.0435x+69.086 | | (1/2)^0 | | 4/21=y/84 | | 4-x=7-3x | | 2-3p=11-6p | | 9/c=27/39 | | -25-4x=5x+19 | | 9/c=17/39 | | 1/2t+3 | | 3k^2+3k+6= | | 10/14=30/m | | 6+2x=6x-2 | | 7x-5y=28 | | 2x-7+3x+2=150 | | -5600.00+200.00x=-2300 | | 42/56=6/f | | -2(2x+4)=12 | | y^2+y=.75 | | 19-5/3x=4 | | 12/7=36/m | | 6/z=3/5 | | 9/g=15/10 | | p=6h/-3+y | | 5u-10=-3u-10 | | p=h+5h/-3+y | | (y-3)(-5y^2+6y+2)= |

Equations solver categories